Empirical study on intra‐regional bond investment: an application to East Asia. (11th March 2020) - Liu, Lian; Cui, Yuming; Lu, Changrong
Abstract : Since the 1997 Asian financial crisis, bond market development has been one of the central pillars of financial cooperation in East Asia, with concerted efforts made by the East Asian economies to integrate regional bond markets. As a result, aggregate intra‐regional bond investment expanded from US$49.56 billion in 2003 to US$352.18 billion in 2017. This paper examines the pattern and determinants of intra‐regional bond investment in East Asia. We analyse regional foreign holdings of long‐term and short‐term bonds in eight East Asian economies. Bond market size turns out to be the main concern of regional foreign investors participating in East Asian long‐term bond markets. This analysis also highlights the importance of bond issuance and bond yield volatility in attracting regional foreign short‐term bond investment. Therefore, initiatives to improve regional bond market development may be crucial to stimulating intra‐regional bond investment and in turn enhance East Asian financial stability.